Generic web platform for manage the bibliographic references using RFId (2007)
It introduces the results of a research project which the objective to develop a system for the bibliographic references using RFId “Radio Frecuency Identification”. In compliance with the ISO 14443 Norm, in a software it was implemented the reading and writing functions for the RFId system, a Web Service was developed to manage the books and as a complement a spiral antenna simulation is shown, which is used generally in RFId tags.